(untitled) (Research, Society and Development, 2022)
Coagulation disorders are scientifically recognized as abnormalities that affect the clotting plasma structure. The most common type of coagulopathy among individuals is Von Willebrand Disease (VWD), seen as a type of hereditary origin, which can manifest from birth, or in some event of adult life, as well as being asymptomatic and undiagnosed., interfering and harming the clotting function of the body of affected individuals. This research aimed to analyze the genetic, clinical and environmental factors that favor and support the accuracy of the diagnosis for VWD. Methodologies of literature review and document analysis were used. It was a research with a qualitative approach, of a basic nature, with descriptive objectives and bibliographic procedure. The results found show that DVW affects the VWF, essential for the clotting process, being considered the most common coagulopathy, despite cases of underreporting of the disease. The conclusion of the research indicates that the accuracy of laboratory diagnosis must take into account genetic and clinical factors, in addition to using screening and additional tests to diagnose the type and subtype of the disease, in order to apply the most effective treatment.